Efficacy Of White Turmeric Solution as A Natural Preservative for Eggs: A 12-Hour Soaking Evaluation on Internal Quality - Krisnaningsih, Aju Tjatur Nugroho; Brihandhono, Ari; Abrori, Yuridlo Jaka (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The present study investigated the influence of a 12-hour soak in white turmeric solutions at varying concentrations on the internal quality characteristics of eggs laid by purebred chickens, assessing its potential as a natural preservation method. This study utilized 64 one-day-old eggs from Isa Brown hens. This study used a complete randomized design in a lab setting with four treatments and four replications. Each replicate consisted of 4 eggs. The eggs were soaked in one of the following solutions of white turmeric for the study: P0: 0%, P1: 15%, P2: 30%, and P3: 45%. The variables observed consisted of egg yolk color, egg white index, egg yolk index, and egg pH. The recorded data were subjected analysis of variance. Least significance difference test was applied to identify which mean populations are statistically different. The results showed that soaking eggs using turmeric white solution had a highly significant effect (P<0.01) on egg yolk color, egg white index, egg yolk index, and egg pH. The average yolk color was highest at P2 (7.69±0.13), egg white index at P2 (0.08±0.01), egg yolk index at P2 (0.44±0.01), lowest pH value at P2 at 7.73 and highest at 9.14 at P0. It can be concluded that the internal quality of purebred chicken eggs can be enhanced by soaking them for 12 hours in a solution of 30% white turmeric, which can be used as a natural preservative.